Sirtuin Control of Mitochondrial Dysfunction, Oxidative Stress, and Inflammation in Chagas Disease Models - Wan, Xianxiu; Garg, Nisha Jain (Frontiers in Cellular and Infection Microbiology, 2021)
Trypanosoma cruzi is a digenetic parasite that requires triatomines and mammalian host to complete its life cycle. T. cruzi replication in mammalian host induces immune-mediated cytotoxic proinflammatory reactions and cellular injuries, which are the common source of reactive oxygen species (ROS) and reactive nitrogen species (RNS) during the acute parasitemic phase. Mitochondrial dysfunction of electron transport chain has been proposed as a major source of superoxide release in the chronic phase of infection, which renders myocardium exposed to sustained oxidative stress and contributes to Chagas disease pathology. Sirtuin 1 (SIRT1) is a class III histone deacetylase that acts as a sensor of redox changes and shapes the mitochondrial metabolism and inflammatory response in the host. In this review, we discuss the molecular mechanisms by which SIRT1 can potentially improve mitochondrial function and control oxidative and inflammatory stress in Chagas disease.